Novel therapies for advanced skin carcinomas - Modrakowska, Paulina; Balik, Karolina; Maj, Małgorzata; Bajek, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Advanced skin carcinomas are a serious therapeutic problem. The statistical analysis shows a continuous increase in the incidence of both melanoma and non-melanoma skin cancers. Traditional therapies are characterized by low effectiveness and patients overall survival is not affected by them. By understanding the molecular pathways that lead to the neoplastic transformation and thanks to the knowledge of the immune system, it is possible to use personalized medicine in novel therapies for advanced skin carcinomas.